Sacitra ullū tantra : ulūka (ullū) śakuna, yantra, mantra, tantra prayoga . - Dīkshita, Rājeśa (Dehātī Pustaka Bhaṇḍāra, 1973)
Manual for fortunetelling and Hindu magic rites using the owl as a medium.